2013
DOI: 10.1264/jsme2.me13023
|View full text |Cite
|
Sign up to set email alerts
|

Diversity and Fermentation Products of Xylose-Utilizing Yeasts Isolated from Buffalo Feces in Thailand

Abstract: Twenty-eight xylose-utilizing yeast strains were isolated by enrichment culture from 11 samples of feces from the rectum of Murrah buffalo and Swamp buffalo in Thailand. On the basis of their morphological and biochemical characteristics, including sequence analysis of the D1/D2 region of the large-subunit ribosomal RNA gene (LSU rDNA), they were identified as Candida tropicalis (designated as Group I, 11 isolates), Candida parasilosis (Group II, 2 isolates), Candida mengyuniae (Group III, 2 isolates), Sporopa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(9 citation statements)
references
References 44 publications
0
9
0
Order By: Relevance
“…Additionally xylose-utilizing species including Candida sp., Geotrichum sp., Sporopachydermis sp., Trichosporon sp., Pichia sp., and Sugiyamaella sp. have been isolated from buffalo feces (Wanlapa et al, 2013 ) or from soil (Zhang et al, 2014 ). Although some success has been achieved using natural xylose fermenting species, their industrial relevance has yet to be demonstrated.…”
Section: Metabolism Of Xylose From Hemicellulose For Bioethanol Produmentioning
confidence: 99%
“…Additionally xylose-utilizing species including Candida sp., Geotrichum sp., Sporopachydermis sp., Trichosporon sp., Pichia sp., and Sugiyamaella sp. have been isolated from buffalo feces (Wanlapa et al, 2013 ) or from soil (Zhang et al, 2014 ). Although some success has been achieved using natural xylose fermenting species, their industrial relevance has yet to be demonstrated.…”
Section: Metabolism Of Xylose From Hemicellulose For Bioethanol Produmentioning
confidence: 99%
“…A number of yeasts isolated in this study produced significant amount of xylitol during growth on 20 g/L xylose. Similarly, Lorliam et al 27 reported that C. tropicalis produced 22.8 g/L of xylitol during growth on 6% xylose. The presence of high concentrations of xylitol could be explained by the redox imbalance that occurs during the conversion of xylose to xylulose, especially under oxygen limiting conditions.…”
Section: Discussionmentioning
confidence: 88%
“…In another study by Lorliam et al . 27 28 xylose utilizing yeasts were isolated from the dung of buffalo. Eleven of these isolates were identified as C. tropicalis .…”
Section: Discussionmentioning
confidence: 99%
“…Very few references exist regarding ethanol production from xylose by fungi of the Geotrichum genus. Lorliam et al (2013) obtained 0.11 g L −1 of ethanol from medium containing 6% xylose and inoculated with an isolate identified as Geotrichum sp . Nigam et al (1985) have isolated four strains of Geotrichum sp .…”
Section: Discussionmentioning
confidence: 99%
“…Microorganisms of interest were isolated from 5-g portions of the previously fragmented plant sample that were transferred to conical flasks containing 50 mL of YNBX medium (0.67% yeast nitrogen base and 3% D-xylose) with 0.02% chloramphenicol ( Lorliam et al, 2013 ). These flasks were incubated at 28 °C for 120 h with stirring at 150 rpm in an orbital incubator (Nova Ética model 430) for prior enrichment of the population of fungi that assimilate D-xylose.…”
Section: Methodsmentioning
confidence: 99%